1985
DOI: 10.1029/jd090id07p13041
|View full text |Cite
|
Sign up to set email alerts
|

Positive ion composition of the high‐latitude summer D region with noctilucent clouds

Abstract: Positive ion composition and electron and total positive ion densities were measured on July 30 (S26/1) and August 13 (S26/2), above Kiruna as part of a multinational rocket campaign to study noctilucent clouds (NLC). Two magnetic ion mass spectrometers took measurements at altitudes of 65-126 km in twilight at times of very low magnetic activity and of NLC sightings at 82.5-83.4 km. The hydration order of the most abundant proton hydrates increased with height from n -3 below 76 km to n = 6 and n = 5 at 88 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 39 publications
2
57
0
Order By: Relevance
“…They speculated that this discrepancy was due to much higher concentrations of H 2 O 2 during summer. In later mass spectrometric measurements (Kopp et al, 1985b), positively charged clusters containing H 2 O 2 were observed in the presence of NLC. Kopp et al (1985b) concluded that the concentration of H 2 O 2 must be higher than expected in order for these clusters to form.…”
Section: Impact Of Ice Particles On the Neutral Chemistry Of The Mesomentioning
confidence: 99%
See 1 more Smart Citation
“…They speculated that this discrepancy was due to much higher concentrations of H 2 O 2 during summer. In later mass spectrometric measurements (Kopp et al, 1985b), positively charged clusters containing H 2 O 2 were observed in the presence of NLC. Kopp et al (1985b) concluded that the concentration of H 2 O 2 must be higher than expected in order for these clusters to form.…”
Section: Impact Of Ice Particles On the Neutral Chemistry Of The Mesomentioning
confidence: 99%
“…In later mass spectrometric measurements (Kopp et al, 1985b), positively charged clusters containing H 2 O 2 were observed in the presence of NLC. Kopp et al (1985b) concluded that the concentration of H 2 O 2 must be higher than expected in order for these clusters to form. The redistribution of water vapour, and subsequently the odd hydrogen species, by the formation of ice particles is most likely the explanation for these enhanced H 2 O 2 concentrations in the summer mesosphere.…”
Section: Impact Of Ice Particles On the Neutral Chemistry Of The Mesomentioning
confidence: 99%
“…The first measurements in the atmosphere on a rocket were by Narcisi and co-workers (15)(16)(17)(18)(19) (21,22). Other rocket measurements were made by Kopp and coworkers at the University of Bern (11)(12)(13)(14), Goldberg and co-workers at NASA Goddard (23)(24)(25), and Arnold and Krankowsky at the MPI-K (26)(27)(28). Previously, measurements in the stratosphere on balloon platforms were made by the group of Arijs and co-workers at the Belgium Institute of Space Technology (29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
Section: If Instrumentationmentioning
confidence: 99%
“…The exception is the magnetic instrument developed by Kopp at the University of Bern (11)(12)(13)(14). The instrumentation used in rocketborne mass spectrometry has been discussed in detail by Arnold and Viggiano (1), and the present review will emphasize lower-altitude measurements and new details for the rocket instrumentation.…”
Section: If Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation